Model Pendidikan Sekolah Islam Terpadu dalam Aspek Managemen: Studi Kasus SMP, SMA, IT Insan Mandiri - Husaini, M.; An Andari; Afif Ansori (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
The study is entitled “Multiple Intelligences-based Islamic Religion Education Learning Management (PAI) at IT Ins Mandiri Cibubur High School”. The aim of this study is to explain how IT High School Insan Mandiri cibubur as an educational institution implemented the concept of “Berganda Intelligencies” to create a learning model based on “Muliple Intelligences”. The authors deliberately took PAI learning as a sample to facilitate the author in the research process as well as not too spread and focus. Because, in fact, this research aims to figure out a model of a comprehensively multiple-based learning concept of intelligence. This research is a kind of qualitative research with a phenomenological approach. The conclusion of this research stated that the application of learning management based on the concept of “Multiple Intelligences” implemented by the Cibubur IT High School includes the process of learning planning, learning implementation and evaluation of learning outcomes. In planning learning, teachers use a student's database of compact intelligence (MIR) research results, this is to make it easier for teachers to draw up a learning implementation plan (RPP), and then teachers can choose a variety of learning strategies and methods, which are adapted to the learning style and intelligence tendencies of students. Then in the implementation of learning, the teacher implements what has already been compiled in the Learning Plan (RCP) that is implemented with interesting learning and enjoyable learning with the aim of triggering various potential students and using "quantum teaching methods" and implementation Al-Qur'an-based projects. (PBQ). The final process is the evaluation of learning outcomes, using authentic assessment methods, called balanced and objective assessments in each area, both cognitive, affective and psychomotor.